(untitled) (Research, Society and Development, 2020)
Starting from the idea that the literacy process is characterized by the appropriation and social use of instruments necessary to meet the social needs of the subject, it is defined as an objective for this investigation to identify, according to the perspectives of teachers, the challenges that are manifested in the literacy process of students with Special Educational Needs. In order to follow the investigative path, we opted for the use of field research, of an exploratory nature with quantitative and qualitative treatment of the results, also using the hypothetical-deductive method by which it was possible to identify the teaching challenges with a group of active teachers in public and private schools in the municipality of Santana / AP that teach students with Educational Needs. We also used the data collection technique known as the Focus Group for the wealth of information that emerged and supported the data analysis. The results obtained showed that the main challenges faced by teachers in the literacy process of special students is the absence of specific technical training to serve this group of students and the significant lack of support from families in their commitment and collaboration with their children’s educational development. , assigning responsibility for this process to teachers and the school.